PENGARUH EARNINGS MANAGEMENT TERHADAP NILAI PERUSAHAAN DIMODERASI DENGAN PRAKTIK CORPORATE GOVERNANCE (Studi Empiris Pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2008 – 2011) - Sri Lestari, Lulus; Pamudji, Sugeng (Diponegoro Journal of Accounting, 2013)
The aims of this research are empirically to find out the influence of earnings management on the firm’s asset, the practice of corporate governance upon the firm’s asset and the influence of practices of corporate governance on the relation between earnings management and the firm’s asset in a hope for understanding the rule of practices of corporate governance toward the practice of earnings management performed by the firm in an effort to increase the firm’s assets. The samples of this research are primarily non financial companies listed in Indonesia Stock Exchange around the years 2008 – 2011. Samples are gathered using the method of purposive sampling and acquired 152 companies. Hypothesis is tested by the use multiple regression analysis. The research reveals that corporate governance has significant effect on the firm’s asset with independent commissioner variable and institutional ownership. Managerial ownership tends to lower the firm’s asset while audit quality certainly increases the asset. Independent commissioner, audit quality, and institutional ownership are among those moderating variables applied for earning management and the firmsassets while managerial ownership is out of moderating variable. Earning management can be minimized by mechanisms of monitoring conducted by independent commissioner, audit quality and institutional ownership.